Defective glucagon secretion after intrahepatic but not non-hepatic islet autotransplantation - Bellin, Melena D. (Am J Transplant, 2014)
Defective glucagon secretion during hypoglycemia after islet transplantation has been reported in animals and humans with type 1 diabetes. To ascertain whether this is true of islets from non-diabetic humans, subjects with autoislet transplantation in the intrahepatic site only (TP/IAT-H) or in intrahepatic plus non-hepatic (TP/IAT-H+NH) sites were studied. Glucagon responses were examined during stepped hypoglycemic clamps. Glucagon and symptom responses during hypoglycemia were virtually absent in subjects who received islets in the hepatic site only (glucagon increment over baseline = 1 +/− 6, pg/ml, mean +/− SE, n = 9, p = ns; symptom score = 1 +/− 1, p=ns). When islets were transplanted in both intrahepatic + non-hepatic sites, glucagon and symptom responses were not significantly different than Control Subjects (TP/IAT-H+NH: glucagon increment = 54 +/− 14, n = 5; symptom score = 7 +/− 3; Control glucagon increment = 67 +/− 15, n = 5; symptom score = 8 +/− 1). In contrast, glucagon responses to intravenous arginine were present in TP/IAT-H recipients (TP/IAT: glucagon response = 37 +/− 8, n=7).). Transplantation of a portion of the islets into a non-hepatic site should be seriously considered in TP/IAT to avoid post-transplant abnormalities in glucagon and symptom responses to hypoglycemia.